gradien:
m = (3-(-2))/((-4)-1)
m = 5/(-5)
m = (-1)

y - y1 = m(x - x1)
y - 3 = (-1)(x + 4)
y = -x - 4 + 3
y = -x - 1

atau enaknya
(-y) = x + 1

Semoga membantu :)

Jawabanmu

2014-03-02T22:18:06+07:00
(2,3) ⇒ x1, y1
(-1,4) ⇒x2, y2

y-y1 per y2-y1 = x-x1 per x2-x1
y-3 per 4-3      = x-2 per -1-2
y-3 per 1          = x-2 per -3
-3y + 9              = x-2
-x - 3y + 9 + 2  = 0
-x - 3y + 11      = 0
x + 3y -11        = 0
2014-03-03T00:14:27+07:00
Garisnya tegak lurus ataubiasa saja?
biasa aja
itu soal isian atau pilihan ganda?
pilihan ganda